Desenvolvimento de queijo petit-suisse com extrato de soja - Andrade, Ana Paula Cristiane de (2014)
Soy has high nutritional quality components, it is considered a functional food, and is used in the development of new products, mostly from soy extract. Derivatives of soy contains no cholesterol and its consumption is indicated for people who are lactose intolerant or allergic to cow's milk. Therefore, the objective of the research is to develop formulations and characterize petit-suisse cheese with soy extract, increasing thus the availability of new industrial products that increase the consumption of this grain as important to human health. After tests of formulations, obtained the best conditions for elaboration of the product: 66% clot, 20% fruit pulp, 13.6% of crystal sugar, artificial coloring 0.1%, 0.1% aroma artificial and 0.2% guar gum and xanthan. Strawberry and passion fruit: two formulations were made of petit-suisse cheese with equal proportions, however, differing only in the flavor of the fruit pulp. Analysis of proximate composition (moisture, protein, lipid, ash), pH and titratable acidity were performed. Sensory acceptance tests were also conducted using the hybrid hedonic scale of 0 to 10 points, and purchase intent, with a five-point hedonic scale. The samples did not show significant differences in ash and lipid determinations. The analysis of pH and acidity, the cheese samples petit-suisse with soy extract and fruit pulps differed among themselves statistically, due to the composition of the fruit pulp. The Cheeses and passion fruit pulps showed more acidic pH levels and high acidity, if compared with the petit-suisse cheese with soy extract strawberry flavor. In the sensory attributes: the flavor, texture and overall acceptance of the samples did not differ among themselves. So the two cheeses made from the extract of soybeans were well accepted by the judges, being found by the assessment of acceptance of purchase, in which the judges 'liked slightly' product. In addition, the formulations were approved by the panel by analyzing purchase intent, where most of the judges 'definitely or probably buy' cheeses.